Morphological, structural and optical behaviour of PVA capped binary (NiO)0.5 (Cr2O3)0.5 nanoparticles produced via single step based thermal technique - Al-Hada N.M.; Kamari H.M.; Saleh M.A.; Flaifel M.H.; Al-Ghaili A.M.; Kasim H.; Baqer A.A.; Saion E.; Jihua W. (Elsevier B.V., 2023)
In this research study, a thermal treatment approach based on a novel single-step has been utilised to addresses the synthesis of binary NiO0.5 Cr2O3 0.5 nanoparticles. Characteristics of these binary metal oxide nanoparticles were examined by employing appropriate characterization tools. Sample patterns of X-ray diffractions were used, calcined with temperature (Temp), set to 500 C revealed the existence of face-centred cubic (fcc) and hexagonal crystalline structures (hcs). It was noted that with a rising calcination temperature, the nanoparticle dispersal was enhanced further. On the other hand, TEM micrographs have been used to calculate the size of the mean particle. It was found that there was a rising tendency with the increased calcination temperature and this the growth of the mean particle. Increased particle size inherited a rise of nanoparticles' photoluminescence intensity, as suggested by recorded spectra, and various energy band gaps. This result would have been reduced as an effect once calcination temperature was increased. Resulting NiO0.5 Cr2O3 0.5 nanoparticles could be used in the realm of semiconductors and energy applications. 2020 The Authors